THE ROLE OF INTENSIVE INSULIN THERAPY ON SUPEROXIDE DISMUTASE (SOD), TUMOR NECROSIS FACTOR-? (TNF-?), AND INTERLEUKIN-6 (IL-6) ON HYPERGLYCEMIA IN CRITICALLY ILL PATIENTS - Wiryana, Made; Suastika, Ketut; Bagianto, Hari; Bakta, Made (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol. 3, No. 1 Januari 2009)
Hyperglycemia and insulin resistance are common in critically ill patientsin the ICU, although they have not previously had diabetes. It has been reportedthat pronounced hyperglycemia may lead to complications in such patients, andcause the reactive oxygen species (ROS) production, although controlled trial dataare still lacking. The current debatable issue, focusing on whether the intensiveinsulin therapy, aimed at normalizing blood glucose, may improvepatients’prognosis. Then, the debate is mainly about the time to start the therapy,and target of blood glucose level. Therefore, this research is mainly designed andaimed at knowing the difference between intensive insulin therapy andconventional insulin therapy on the increase of superoxide dismutase (SOD),decrease of cytokine production (TNF-? and IL-6), increase of albumin level, andevent of SIRSThis study was carried out in a randomly pre and post-test control groupdesign, involving 40 adult patients being nursed through the ICU Sanglah hospitalDenpasar. They were randomly assigned to receive intensive insulin therapy, inwhich blood glucose was decreased and maintained at the level between 80-110mg/dl, or conventional insulin therapy in which the insulin was infused only if theblood glucose level exceeded 215 mg/dl, decreased and maintained then at thelevel between 180-200 mg/dl.The result of the study showed that there was (1) significant increase ofSOD mean level (370. 70 vs 98.50 U/gHb, p=0.001); (2) no significant decreaseof TNF-? mean level; (3) significant decrease of IL-6 mean level (10.26 vs 2.25;p=0.023); (4) significant increase of albumin mean level ( 0.62 vs 0.22); (5)significant decrease of SIRS (10 % vs 40 %, p=0.000) on intensive insulin therapygroup compared to conventional insulin therapy group. It can be concluded thatintensive insulin therapy could maintain blood glucose level between 80 – 110mg/dl, increase SOD level, decrease IL-6 level, increase albumin level, anddecrease SIRS on hyperglycemia in critically ill ICU patients.
Keywords: hyperglycemia, intensive insulin therapy, conventional insulin therapy, super oxide dismutase (SOD), critically ill patients, proinflammatory cytokine, albumin, and SIRS.